Antigenic drift of Haemophilus influenzae in patients with chronic obstructive pulmonary disease. - Groeneveld, K (1989)
Differences in the major outer membrane protein b,c (molecular weight, 39,000 to 41,000) of related Haemophilus influenzae strains isolated from the sputum of patients with chronic obstructive pulmonary disease were analyzed biochemically and immunologically. Protein b,c was isolated from a total of six related H. influenzae strains from two chronic obstructive pulmonary disease patients. After CNBr digestion of the proteins, the differences in size appeared in the larger of the two fragments. Trypsin and chymotrypsin digests of proteins from related H. influenzae strains showed that proteins differed by only a few peptides or were very similar, in contrast to the peptide maps of proteins from nonrelated strains. Peptide analysis of b,c proteins from related H. influenzae strains by high-performance liquid chromatography after Staphylococcus aureus V8 protease digestion and amino acid analysis of corresponding fractions revealed highly comparable patterns, indicating only minor differences in the amino acid sequences of these proteins. Immunization of rabbits with intact bacteria of four related H. influenzae strains resulted in a strong anti-protein b,c antibody response in all animals. In three of four rabbits, antibodies specific for the b,c protein of the strain used for immunization were elicited, indicating that the changed proteins contained specific immunodominant epitopes. Anti-protein b,c antibodies promoted strain-specific, complement-dependent, bactericidal activity. From these results, we conclude that H. influenzae shows antigenic drift in immunodominant epitopes, caused by small changes in amino acid composition of the b,c protein. Antibodies to these epitopes promote complement-dependent bactericidal activity.